Ionic Interactions of Fe2+ and Cu2+ in Aqueous Methanol System - PERVEEN, ABIDA; IMAM NAQVI, IFTIKHAR; SAEED, REHANA (Asian Journal of Chemistry, 2010)
The densities and viscosities of FeSO4 and CuSO4 solutions in aqueous methanol (10, 30 and 50 % v/v systems) within a concentration of 1 × 10-2 to 9 × 10-2 mol/dm3 at 30, 40 and 50 ºC have been measured. It was observed that the viscosities of solutions increase with the increase in concentration of salt and solvent composition at particular temperature. The viscosity data was used to evaluate ion-ion interactions and ion - solvent interactions in terms of A and B coefficients of Jones-Dole equation. The values of ion solvent interaction were incorporated in terms of Jones Dole coefficient 'B'. It was found that the values of B increased from FeSO4 to CuSO4 with the increase in temperature from 30, 40 and 50 ºC. Apparent molar volumes (φV) were derived from these data supplemented with their densities respectively. The limiting apparent molar volumes (φVº) and experimental slopes (Sv) obtained from Masson equation have been interpreted in terms of ion-ion and ion-solvent interactions, respectively.